Interaction in online tutoring sessions: an opportunity to knit english language learning in a blended program (2009)
This article reports a research study which intended to describe the interaction taking place between a tutor and her students during the online tutoring sessions (ots ) in the alex Virtual English Program at the Universidad Nacional de Colombia, in Bogotá. Students’ surveys, chat transcriptions and tutor’s journals were used to collect data. The results showed how language itself, the methodology of the course, reflection upon learning, and social and personal issues made up the conversational topics prevailing in these sessions. It was also found that the main interactions between the tutor and the learners consisted of double-way dynamics. Key words: Interaction, online tutoring sessions, alex Virtual English Program, blended program Este artículo reporta un trabajo investigativo que buscó describir la interacción que tuvo lugar entre una tutora y sus estudiantes durante las tutorías en línea (tl ) en el programa alex Virtual-Inglés de la Universidad Nacional de Colombia, en Bogotá. Para recolectar información se usaron encuestas a los estudiantes, transcripciones de chat y diarios de la tutora. Los resultados mostraron cómo la lengua en sí misma, la metodología del curso, la reflexión sobre el aprendizaje y los asuntos sociales y personales configuraban los temas de conversación predominantes en estas sesiones. También se encontró que las interacciones principales entre la tutora y los estudiantes consistían en dinámicas de doble vía. Palabras clave: Interacción, tutorías en línea, Programa alex Virtual–Inglés, programa mixto